Analisis proses pembuatan kalender berbahan dasar kertas daur ulang dengan campuran bunga telang menggunakan pendekatan 5W1H - Jaka Santosa; Sahiba Sahila; Rachmah Nanda Kartika; Rafi Aditama; Muhammad Ivan Maulana; Mafaid Rizky Pratama; Musthofa (Jurnal Teknik Industri dan Manajemen Rekayasa, 2026)
Commercial calendar production typically uses virgin paper, contributing to increased wood fiber consumption and waste. This condition encourages the development of environmentally friendly alternatives using recycled materials. This study aims to produce a desk calendar made from recycled paper mixed with butterfly pea flowers as a natural dye and aesthetic element, and to evaluate the effectiveness of its production process.The study involved several stages, including recycled paper processing (soaking, pulping, mixing with butterfly pea petals, sheet forming, drying, and cutting) and calendar assembly (cutting carton board, applying linen cover, printing A5 calendar design, punching spiral holes, installing spiral wire, and attaching a 7×7 cm glass component). The production process was evaluated using the 5W1H framework to identify key factors, constraints, and methodological effectiveness.The resulting calendar displays natural visual characteristics,coloration from butterfly pea pigment, and an additional functional element through the integration of a small glass piece. Analysis shows that paper-making is the most time-consuming stage, while the assembly process is relatively efficient.The recycled paper calendar incorporating butterfly pea flowers was successfully developed as an eco-friendly product with strong aesthetic value and added functionality. Further improvements are recommended for achieving consistent paper thickness and optimizing drying time.